2008 International Symposium on Information Technology 2008
DOI: 10.1109/itsim.2008.4632022
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of dengue outbreak prediction in Malaysia: A comparison of Neural Network and Nonlinear Regression Model

Abstract: Malaysia has a good dengue surveillance system but there have been insufficient findings on suitable model to predict future dengue outbreak. This study aims to design a Neural Network Model (NNM) and Nonlinear Regression Model (NLRM) using different architectures and parameters incorporating time series, location and rainfall data to define the best architecture for early prediction of dengue outbreak. Four architecture of NNM and NLRM were developed in this study. Architecture I involved only dengue cases da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Similarly, Husin et al [12] compared the NN with a nonlinear regression model (NLRM). Their comparison on applying the NN and NLRM to the same data (i.e., the same five Malaysian cities as Yusof and Mustaffa) showed that the NN led to smaller mean square errors (MSE): 0.028 for the NN and 26.054 for the NLRM.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Husin et al [12] compared the NN with a nonlinear regression model (NLRM). Their comparison on applying the NN and NLRM to the same data (i.e., the same five Malaysian cities as Yusof and Mustaffa) showed that the NN led to smaller mean square errors (MSE): 0.028 for the NN and 26.054 for the NLRM.…”
Section: Related Workmentioning
confidence: 99%
“…Due to the relation between weather conditions and the proliferation of the dengue vector mosquito, statistical and machine-learning models can be used for forecasting the number of dengue cases based on weather conditions [11,12,21]. The detection of such outbreaks in advance would give to public health agencies time for dealing with the high number of cases and even decrease them.…”
Section: Introductionmentioning
confidence: 99%
“…Normalization is mainly helpful for classification, as it progress accuracy and efficiency of mining. There are three types of normalization techniques namely Z-Score Normalization [11], Decimal Point Normalization [12], and Min-Max Normalization [13]. In Z(Zero Mean)-Score Normalization, the data is normalized based on the mean and standard deviation.…”
Section: Dsaraswathi Akrishnakumarmentioning
confidence: 99%
“…The oldest and most widely used ANNs are feedforward neural networks with backpropagation learning rule (Rumelhart et al, 1986). Husin et al (2008) developed an ANN and a nonlinear regression model to predict dengue outbreaks in Malaysia and compared the results of those two methods. They examined weekly dengue cases in five districts for the years 2004-2005.…”
Section: Approaches To Modeling and Their Evaluationmentioning
confidence: 99%